1995
DOI: 10.1016/1357-2725(95)00047-s
|View full text |Cite
|
Sign up to set email alerts
|

Immunoquantification of type I, III, IV and V collagen in small samples of human lung parenchyma

Abstract: Please be advised that this information was generated on 2018-05-09 and may be subject to change. Pergamon 1357-2725(95)00047-XCopyright © 1995 Elsevier Science Ltd Printed in Great Britain. All rights reserved 1357-2725/95 $9.50 + 0.00 Blochem. Ceil Biol. Vol. 27, No. 8, pp. 775-782, 1995

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Lung allografts are also susceptible to injuries by exogenous pathogens and gastroesophageal reflux (10 -12, 29 -31), creating an inflammatory milieu conducive for the development of autoimmunity. We found that immune responses could be elicited in LT patients against col-V, a minor component of lung collagen (32). During inflammation and lung tissue repair, the col-V levels in the lungs increase significantly (33,34).…”
Section: Discussionmentioning
confidence: 88%
“…Lung allografts are also susceptible to injuries by exogenous pathogens and gastroesophageal reflux (10 -12, 29 -31), creating an inflammatory milieu conducive for the development of autoimmunity. We found that immune responses could be elicited in LT patients against col-V, a minor component of lung collagen (32). During inflammation and lung tissue repair, the col-V levels in the lungs increase significantly (33,34).…”
Section: Discussionmentioning
confidence: 88%
“…Col-V is a minor collagen in the lung (36). During inflammation and lung tissue repair, the col-V levels in the lungs increase significantly (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…In lung transplantation, one such cryptic self-antigen is collagen type-V (col[V]) (2). Col(V) is classified as a minor fibrillar collagen and, in the human lung, the ratio of matrix collagens is 86:28:8:1.6 (for collagens I, III, IV, and V, respectively) (7). Under normal physiologic conditions, col(V) coassembles into heterotypic fibrils with the major fibrillar collagen type I (8,9).…”
mentioning
confidence: 99%